Variability and error in measurement of infant formula powder and water: an experimental study - Rosenkranz, Richard R.; Gonzalez-Alvarez, Ana; Acosta, Chris; Hooyman, Andrew; Hidalgo, Jose R.; Ballesteros-Paniagua, CindyRomina; Rosenkranz, Sara K. (Frontiers in Nutrition, 2024)
Formula feeding is the only viable nutrition alternative for infants 0-6mos who cannot breastfeed. Among the drawbacks of formula feeding, however, is potential dilution or concentration errors in the formula during preparation that may lead to infant health issues. The present study aimed to investigate the accuracy of caregiver measurements as they prepared infant formula under multiple conditions, compared with manufacturer specifications. A diverse sample of caregivers (N = 84) participated in this cross-over experimental study. Participants hand-scooped infant formula powder and poured water to prepare 4oz and 7oz feedings, using both a standardized set of infant formula products and participants' own products. Linear mixed effects models were used to estimate fixed effects of target amount (4oz versus 7oz) and products (participant versus researcher) on mean absolute percent error (MAPE) of measurement. Across all conditions MAPE was significantly greater for measuring powder than for water (9.0% vs. 4.4%; p<0.001) with a combined powder and water MAPE at 13.0%. Greater measurement error was associated with the odd-sized 7oz preparation and participants' own products. We observed considerable variability and substantial error during infant formula preparation, particularly for hand-scooping of powder, which tended toward higher values than the theoretical gold standard.